Writing at university : a guide for students - Creme, Phyllis, 1942-; Lea, Mary R., (Mary Rosalind), 1950- (Buckingham ; Philadelphia PA : Open University Press, 1997)
This book is about: You and university writing; First thoughts on writing assignments; Writing for different courses; Beginning with the title; Reading as part of writing; ...
Keywords: Academic writing; Rhetoric; English writing; English writing -- Rhetoric; Academic writing